PRICE AND RETURN MODELS--IMPERICAL TESTS OF CHINESE STOCK MARKET - Ye, Chongchong (2008)
In accounting researches, price and return models are usually evaluated and compared, aiming at to select the better one. In both models, earnings response coefficient is the key variable and is paid major attentions to my most previous researches. In previous researches, price and return models as well as other models transformed from original price and return models are universally studied. The general conclusion is: proved by regression analyses, price model is outstanding in economic explanatory power and less biased; meanwhile return model yields more satisfying econometric effects and more reliable in regression results. In this report dataset selected from Chinese stock market is analyzed to compare the effects of price and return models when they are applied under different market environment. The properties and characteristics of 4 different models are theoretically analyzed and tested with accounting data. The outcomes are generally identical with other researches in different markets, American stock market for example. However when earnings response coefficient is regressed on interest rate, the returns of Chinese data are significantly different from that of American data. Governmental interference and regulation against the macro economy is regarded as the causation. The noise element in earnings information and the non-linearity problem caused by price deflation is not further investigated, which are parts of the recognized limitations.